HAEMORRHAGE INTRACEREBRAL SPONTAN SETELAH HEMODIALISIS: SPONTANEOUS INTRACEREBRAL HAEMORRHAGE AFTER HAEMODIALYSIS - Ronny Yoesyanto; Andika Surya Atmadja (Neurologi Manado, 2019)
Haemodialysis (HD) is one of therapy for patient with chronic renal failure. During HD, patient will be given heparin in certain dose to prevent blood clotting. The using of heparin will increase the risk of intracranial bleeding, although it rarely occur. A 60 year old man suddenly got tonic clonic seizure for about 30 seconds right after he finished his routine HD. It was his first seizure. During the seizure, the patient lost his consciousness but the patient regain his consciousness after the seizure stopped. After the seizure, he has an anterograde amnesia.